DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON MICROSOFT SWAY TO IMPROVE SPATIAL THINKING SKILLS - Ika Listiqowati; Iwan Alim Saputra; Rendra Zainal Maliki; Khairurraziq Khairurraziq; Arifuddin Abd Muis (JURNAL EDUSCIENCE, 2026)
Purpose - This study aims to develop an interactive learning media in Microsoft Sway to enhance participants' spatial thinking skills.Methodology - Method study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study population consisted of grade 11 students at SMA N 1 Banawa across 8 classes. A sample of 30 participants was drawn from class XI C IPS. The instrument included 1) tests to think spatially as a pre-test and post-test, 2) questionnaire validation and eligibility expert technology learning, and 3) questionnaire teacher and participant responses to educate. Analyse data for effectiveness testing using the N-Gain test. Eligibility was measured based on expert validator results, technology learning outcomes, teacher and participant responses, and the educational use percentage formula.Findings - Research results obtained results validation media expert with a score of 96.2 is included in the excellent category, or worthy, which is Very worthy, and did need to be revised; however, for perfection, the fixed validator product provides suggestions for improvement. From the effectiveness test, an N-gain value of 0.50, or an enter criterion of medium, was obtained, indicating that Microsoft Sway interactive media was developed effectively to improve spatial thinking. "Feasibility test results based on teacher and participant responses yielded scores of 82 and 86, respectively, both classified as Good. This indicates the media is suitable for use and requires no revision. The interactive media developed in Microsoft Sway is practical and feasible for enhancing participants' spatial thinking skills.Contribution - This research provides a positive contribution to the application of technology, media, and digital teaching materials. Suggestions for future researchers include developing interactive Microsoft Sway-based media for other learning materials or subjects and conducting product trials on a broader scale.